Polyphenol and exercise-induced molecular crosstalk: a new frontier in brain function, head and neck cancer therapy, and healthy lifespan extension - Mao, XiuLei; Yang, Sha (Frontiers in Nutrition, 2025)
Emerging evidence highlights the synergistic potential of polyphenols and exercise in modulating molecular pathways critical for brain function, tumor suppression, and healthy aging. Both interventions independently influence oxidative stress, inflammation, apoptosis, autophagy, metabolic regulation, and neuroplasticity—key processes implicated in head and neck cancers (HNCs) development, neurodegeneration, and lifespan determination. Recent studies reveal that polyphenols, through their antioxidant and epigenetic-modifying properties, enhance neuronal resilience, suppress tumorigenesis, and improve metabolic homeostasis. Simultaneously, exercise activates signaling cascades, promoting neurogenesis, immune modulation, and anti-cancer effects. The molecular crosstalk between polyphenol intake and physical activity appears to amplify protective mechanisms, offering novel therapeutic strategies for brain health preservation, HNCs management, and metabolic optimization. This review critically examines the interconnected pathways influenced by polyphenols and exercise, their combined impact on brain function and tumor suppression, and discusses the translational potential for extending healthy lifespan through integrated lifestyle interventions.